Integrated pest management modules in sesame (Sesamum indicum) at Tikamgarh, Madhya Pradesh - GUPTA, M P (The Indian Journal of Agricultural Sciences, 2014)
Three integrated pest management modules, formulated on the basis of previous years research work, were tested against the incidence of leaf roller or capsule-borer (Antigastra catalaunalis Duponchel) and budfly (Dasyneura sesami Grover and Prasad) pests of sesame (Sesamum indicum L.) during the rainy season of 2000 and 2001 at TiKamgarh, Madhya Pradesh. Module M1 comprised moderately resistant variety’JT 21 and 2 follar sprays of neem oil 1%, whereas in module M2 and M3 sesame was intercropped respectively with pigeonpea [Cajanus cajan ( L.) Millsp.] and blackgram (Phaseolus mungo L.) in 3:1 row ratio along with 2 foliar sprays of neem oil 1% as MI. These 3 modules were compared with untreated module, M4. The incidence of leaf roller or capsule-borer and budfly was significantly reduced in module rvfl. The incidence of both the pests was further reduced when sesame crop was intercropped either with pigeonpea or blackgram in modules M2 and M3. Seed-equivalent yield was also significantly increased in module Ml (2 foliar sprays of neem oil) to the extent of 419 kg/ha compared with 271 kg/ha in untreated module M4, which WfLS further increased to 570 kg/ha in module M3 (intercropping with blackgram+neem oil) and to the maximum of 619 kg/ha in module M2 (intercropping with pigeonpea+neem oil). Maximum net profit and incremental cost benofit ratio were earned with module M2 (Rs 4 75S/ha and 6.87), followed by M3 (Rs 4 024/ha and 6.29) and MI (Rs 1 698/ha and 3.53).